Maximizing the utility of available root zone soil moisture data for drought monitoring purposes in the Upper Colorado River Basin and western High Plains, and assessing the interregional importance of root zone soil moisture on warm season water balance - Goble, Peter, author; Schumacher, Russ, advisor; Denning, Scott, committee member; Chávez, José, committee member (Colorado State University. Libraries, 2016)
To view the abstract, please see the full text of the document.
Keywords: drought; moisture; soil; forecast; Colorado; precipitation